Estudo bibliográfico das definições das estratégias de aprendizagem a partir dos estudos de Oxford (2017) - SANTOS, Raí dos (2024)
The study of learning strategies is not new, but it is still relevant when it comes to teaching and learning languages. Understanding how the construct has been defined and the relationship of these definitions with the socio-cultural context can help teachers and learners to enhance language learning. The present work aims to understand how the conceptions of learning strategies have evolved over the years and how this appears in Oxford studies (1990; 2017). We used bibliographical research based on works in the area (Gaignoux, 2006; Oxford, 2017). We analyzed the results of the Oxford (2017) studies and organized the definitions in order to identify similarities. The result showed that the definitions of learning strategies are dynamic and emergent, as they are intertwined in the interaction with/in the context.